2014
DOI: 10.1111/prd.12067
|View full text |Cite
|
Sign up to set email alerts
|

Lasers in periodontal therapy

Abstract: About 50 years ago, lasers started to be used in periodontal treatment following evidence that wounds produced in animals healed more quickly after being irradiated with low-intensity lasers. Increased production of growth factors, stimulated mainly by red and infrared lasers, may participate in this process by influencing the behavior of various types of cells. High-intensity lasers have been used as an alternative to nonsurgical periodontal therapy in root biomodification and to reduce dentin hypersensivity;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 166 publications
0
60
0
11
Order By: Relevance
“…Also according to Dukic (2012) the results of the two treatments are similar in terms of plaque index, bleeding on probing and clinical attachment level: the addition of laser therapy showed a marked improvement in PD, but only in periodontal pockets of moderate depth (from 4 to 6 mm) (39). Finally, because of the biostimulant effect (29,(40)(41)(42), laser therapy induces the acceleration of mitotic processes within the irradiated tissues, without causing structural and/or functional alterations. According to the studies of Benedicenti (2008), the laser would stimulate mitochondrial activity, with a production of intracellular ATP >22% in irradiated cells compared to those not exposed to radiant energy, resulting in a halving of the times of cell duplication (43).…”
Section: Middle Value Pmentioning
confidence: 83%
See 1 more Smart Citation
“…Also according to Dukic (2012) the results of the two treatments are similar in terms of plaque index, bleeding on probing and clinical attachment level: the addition of laser therapy showed a marked improvement in PD, but only in periodontal pockets of moderate depth (from 4 to 6 mm) (39). Finally, because of the biostimulant effect (29,(40)(41)(42), laser therapy induces the acceleration of mitotic processes within the irradiated tissues, without causing structural and/or functional alterations. According to the studies of Benedicenti (2008), the laser would stimulate mitochondrial activity, with a production of intracellular ATP >22% in irradiated cells compared to those not exposed to radiant energy, resulting in a halving of the times of cell duplication (43).…”
Section: Middle Value Pmentioning
confidence: 83%
“…Regarding the tolerance and compliance of the patient, the laser therapy of periodontal pockets does not involve discomfort or intraoperative pain, nor requires, as a rule, the execution of loco-regional anesthesia, since the power values provided are relatively low (3 W) and the energy is supplied in pulsed mode (41). While recognizing these indisputable results, it should be stressed, however, that the laser acts only as an adjunct to etiological non-surgical periodontal therapy, not being able to replace traditional mechanical procedures of SRP; in this regard, the study of Kamma et al (2009) showed that combining mechanical treatment (SRP) with diode laser therapy produces better results than the laser therapy alone, both in clinical (probing depth and clinical attachment level) and bacteriological terms (total bacterial count of periodontal pathogens) (20).…”
Section: Middle Value Pmentioning
confidence: 99%
“…Based on the 28 reviews in Table 3, one might conclude that the aggregate of evidence indicates that lasers have little to no clinical benefit and, because of poor study design, there remains a need for well‐designed clinical trials. Two of the 28 reviews might be viewed as offering support for lasers in periodontal therapy, 62 , 67 five reviews offer equivocating conclusions, 52,57,59,72,76 and the remaining 21 reviews (78%) concluded there is insufficient, inconclusive, or no evidence showing that lasers provide additional benefit when used adjunctive to traditional non‐surgical therapy.…”
Section: The Datamentioning
confidence: 99%
“…Uma revisão publicada recentemente por nosso grupo de pesquisa (PASSANEZI et al, 2015) mostrou que a terapia fotodinâmica em Periodontia parece ser uma alternativa terapêutica promissora. Há a redução de bactérias em biofilmes bucais e sobre implantes, sendo que, no tratamento periodontal, é rotineiro desagregar o biofilme através de raspagem e alisamento radicular, otimizando o efeito de fototoxicidade da aPDT.…”
Section: Revisão De Literaturaunclassified